CLINICAL AND LABORATORY FEATURES OF ACUTE VIRAL HEPATITIS IN THE REPUBLIC OF KARAKALPAKSTAN - Sharibaev Islambek Tursinbaevich, (TADQIQOTLAR, 2026)
Acute viral hepatitis (AVH) remains a significant public health concern in the Republic of Karakalpakstan, contributing to high morbidity among adults and children. This  study  aimed  to  evaluate  the  clinical  presentations  and  laboratory  findings  of patients with AVH in the region. A total of 125 patients with confirmed AVH were included. Clinical symptoms, biochemical parameters, and serological markers were analyzed.  Fever,  jaundice,  and  hepatomegaly  were  the  most  common  clinical manifestations.  Elevated  levels  of  alanine  aminotransferase  (ALT)  and  aspartate aminotransferase  (AST)  were  observed  in  88%  and  85%  of  patients,  respectively. Serological tests revealed hepatitis A virus (HAV) in 42%, hepatitis B virus (HBV) in 35%, and hepatitis E virus (HEV) in 18% of cases. These findings provide important insights  into  the  epidemiology  and  laboratory  characteristics  of  AVH  in Karakalpakstan,  which  may  guide  early  diagnosis,  management,  and  prevention strategies.